Ageing is associated with increased variability of cellular reprogramming and wound healing - Schmidt, Constanze; Kallenberger, Stefan M. (Cardiovascular research, 2020)
Commentary on ‘Heterogeneity in old fibroblasts is linked to variability in reprogramming and wound healing’, by S. Mahmoudi et al., Nature, 2019.1Understanding the determinants of ageing and senescence of cells as part of functional tissues has many implications in translational medicine and is highly relevant for improving treatments of degenerative cardiovascular diseases. The development of methods to create induced pluripotent stem cells (iPSCs) revolutionized the perspectives in regenerative medicine. In 2006, Takahashi and Yamanaka2 first created protocols for establishing iPSCs from murine and later from human tissues. iPSCs are derived through reprogramming of somatic cells by introduction of transcription factors Oct3/4, Sox2, c-Myc, and Klf4.2 Today iPSCs are used to create models for studying cardiovascular diseases, drug effects and for developmental research. During the last years, reprogramming strategies were developed to generate human iPSCs from various tissues such as keratinocytes, blood cells, extramedullary tissue as well as fibroblasts, and to differentiate iPSCs into several types of cells including cardiomyocytes (Figure 1A).3-5 However, the success in creating iPSCs largely differs between tissues, indicating that the cellular origin may determine the reprogramming efficiency. Today, differentiating iPSCs to cardiac cells represents a promising approach in curing degenerative cardiovascular diseases as myocardial infarction or cardiomyopathies.